EFEKTIVITAS PENGGUNAAN MODEL KOOPERATIF TIPE PICTURE AND PICTURE TERHADAP HASIL BELAJAR PELAJARAN SEJARAH DI SMAN 10 PONTIANAK - Dimin, Aristi; Buwono, Sri; Chalimi, Ika Rahmatika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to examine the usage effectiveness of picture and picture learning models towards the learning outcomes of 11th grade students in Senior High School Number 10 (SMAN 10) in Pontianak. The research methodology used in this study is static-design experiment with 2 groups. The research subject was 11th grade students in SMAN 10 Pontianak. Further, XI IPS 2 consisted of 31 students serves as the control class, while the experiment class was XI IPS 3 (30 students). Research procedures consist of planning, implementation, and final stages. The data collected was in form of post test result from both control and experiment classes. Data collection techniques utilized in this research were direct observations, measurement, and documentary study techniques. Data collection instruments encompassed learning outcome test, observation sheet, and documentations. Data analysis used validity, reliability, normality, homogeneity, and independent sample T-tests. The use of picture and picture model found a difference in learning outcomes from control and experiment classes. The analysis result of hypothesis testing by using independent T-test shows a significant value in post test score, 0.000< 0.05. Thus, it can inferring that H0 is rejected, while Ha is accepted. This study concludes that the use of picture and picture model is effective toward the learning outcomes of history subject of students in SMAN 10 Pontianak.Â Keywords: Effectiveness of Picture and Picture Learning Model Usage, Learning Outcomes, History Subject